Structural and magnetic properties of Sr(4-x)M(x)IrO(6) (M=Ca, Zn, Cd, Li, Na) - Segal, N; Vente, J; Bush, T; Battle, P (1996)
The compounds Sr4-xCaxIrO6 (x = 0.5, 1, 2, 3, 4) and Sr3MIrO6 (M = Li, Na, Zn, Cd) have been synthesized and studied by X-ray powder diffraction and SQUID magnetometry. They all adopt the K4CdCl6 structure, with the cations M and Ca occupying only the trigonal prismatic sites in the [001] chains unless x> 1. Those compounds which contain only IrIV order antiferromagnetically at temperatures between 14 and 22 K, and those which contain only IrV show temperature-independent paramagnetism. The development of a self-consistent interatomic potential for the IrIV-O interaction is described. The lattice parameters predicted for the K4CdCl6-like phases using this new potential agree with the experimental values to within ca. 2%.